PELAKSANAAN PENYELIDIKAN DAN PENYIDIKAN KEPOLISIAN TERHADAP ANAK PELAKU TINDAK PIDANA PENCABULAN (STUDI DI POLRES KOTA MEDAN) - Wilson Raja Ganda Tambunan; Muhammad Hamdan; Madiasa Ablisar; Muhammad Ekaputra (Universitas Sumatera Utara, 2017)
ABSTRACT A crime or criminal act is a social phenomenon that occurs in the society. It develops as the society grows and develops. An example of crime found in society is sexual crime such as lascivious molestation. This crime has a quite high rate in Medan. In the last five years, its rate increased either committed by adults or by juvenile. The problems of the research are what factors cause lascivious molestation and why its rate is getting increased in Medan, what policy has been made by Medan Municipality Police in the investigation and verification of the criminal of lascivious molestation observed from the Law No.2/2002 and Law No.11/2012, and how about the obstructions encountered by Police in their investigation regarding the lascivious molestation in Medan. The results found that the factors causing lascivious molestation are free sex, narcotics, dating, technology, faith, lack of parental supervision, alcoholic influence, and unemployment, while the factors increasing the rate of lascivious molestation in Medan are free sex, environment, and low level of education and economy, law enforcement that has not brought a intimidated effect on the criminals, the lack of efforts made by government, technology abuse, and lack of parental debriefing regarding the ethics in juvenile interactions. The investigation and verification upon juvenile criminal of lascivious molestation by Medan Municipality Police has been performed in accordance with the Law No.2/2002 and the Law No.11/2012. The obstruction encountered by the police in their investigation is the difficulty in finding a witness. The research concludes that there is a need for a better society, consistent law enforcer, particularly police, and that the police make use of evidence pursuant to the Criminal Procedure Code. Keywords: Investigation, Verification, Juvenile Criminal of Lascivious Molestatiom